Optimalisasi Promosi dan Pencatatan Keuangan Sebagai Upaya Peningkatan Penjualan UMKM Simping Semprong Hj. Entin: Pengabdian - Halimatussadiyah; Khotmah Navis Anjani; Asiilah; Vita Evelin Handayani Sinaga (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to assist the UMKM Simping Semprong Hj. Entin in overcoming challenges related to promotion and financial recording through targeted mentoring. The population consists of the business owner, two employees, and all transaction records, while the sample includes the entire population for the owner and employees, along with 30 days of transactions selected purposively. The research employed a qualitative descriptive method through observation and interviews. The results indicate an improvement in promotional abilities through the separation of business accounts, enhanced banner design, and more consistent content creation. In addition, financial recording became more structured through the use of receipts and a daily cash book, enabling the business owner to more easily monitor cash flow and evaluate sales performance.